The Performance of the Principal of MTs Safinatun Najah as a Supervisor in Fostering Teacher Professionalism - Muhammad Kudra (Wasatha: Jurnal Studi Islam dan Humaniora, 2024)
This research discusses the performance of the Headmaster of MTs Safinatun Najah as a supervisor in fostering teacher professionalism at Lembaga Pendidikan Dayah Safinatun Najah. The research methodology employs a qualitative approach with a case study design. Data and data sources encompass both primary and secondary data. Data collection involves observation, documentation, and interviews. The research outlines findings regarding the headmaster’s performance as a supervisor in building teacher professionalism at MTs Safinatun Najah. Various approaches and stages of supervision carried out by the headmaster, along with techniques used to enhance teacher professionalism, are expounded upon. The findings indicate that the headmaster undertakes stages of planning, implementation, and evaluation of supervision. Direct approaches involving classroom visits and personal meetings with teachers are used to provide guidance. Additionally, the headmaster’s strategy in cultivating teacher professionalism involves teacher meetings, classroom visits, group work meetings, and teacher performance evaluation. The evaluation of teacher performance and positive changes in teaching practices and behavior signify the success of professionalism development efforts. Overall, the headmaster at MTs Safinatun Najah adopts a participatory approach focused on collaboration and the improvement of educational quality.